Description of Tuber malenconii mycorrhizae and a comparison with mycorrhizae of T. aestivum and T. mesentericum - Garcia-Montero, Luis G.; Di Massimo, Gabriella; Manjon, Jose L.; Velazquez, Javier (MYCOTAXON, 2008)
Tuber malenconii is a recently described uncommon European truffle associated with Quercus ilex that is potentially detrimental to the cultivation of the highly prized edible, T. melanosporum. Examination of T. malenconii mycorrhizae synthesized from fresh ascocarps revealed polygonal mantle cells and numerous cystidia with basal-forked ramifications. Differences between T. malenconii, T. mesentericum, and T. aestivum mycorrhizae are noted; compound and scanning electron micrographs provide additional comparisons.
The following values have no corresponding Zotero field: pub-location: PO BOX 264, ITHACA, NY 14851-0264 USA publisher: MYCOTAXON LTD
Keywords: Ectomycorrhizae; hypogeous fungus; Tuberaceae

Description of Tuber malenconii mycorrhizae and a comparison with mycorrhizae of T. aestivum and T. mesentericum (MYCOTAXON, 2008)
Tuber malenconii is a recently described uncommon European truffle associated with Quercus ilex that is potentially detrimental to the cultivation of the highly prized edible, T. melanosporum. Examination of T. malenconii mycorrhizae synthesized from fresh ascocarps revealed polygonal mantle cells and numerous cystidia with basal-forked ramifications. Differences between T. malenconii, T. mesentericum, and T. aestivum mycorrhizae are noted; compound and scanning electron micrographs provide additional comparisons.

New data on ectomycorrhizae and soils of the Chinese truffles Tuber pseudoexcavatum and Tuber indicum, and their impact on truffle cultivation. - Garcia-Montero, Luis G.; Di Massimo, Gabriella; Manjon, Jose L.; García-Abril, Antonio (Mycorrhiza, 2008)
Chinese truffles serve as a good complement to the market for Tuber melanosporum (Périgord black truffle). However, Chinese truffles could be introduced accidentally or fraudulently into the plantations of Mediterranean truffles, and they could have a negative effect on truffle production and natural ecosystems. The study of Tuber species from China which are commercialized in Europe began 14 years ago. Tuber pseudoexcavatum was proposed as a new species, and this has been validated by some authors based on molecular and phylogenetic studies. We synthesize their ectomycorrhizae using samples from the type collection, and we compare T. pseudoexcavatum and Tuber indicum ectomycorrhizae. The ectomycorrhizae of these species have a morphology which is related to the ectomycorrhizae of T. melanosporum. We provide useful information for the rapid screening of the above-mentioned Chinese truffles ectomycorrhizae, for the quality control of commercial plants mycorrhized with Tuber. Moreover, we analyze the soil tolerance and the host plant affinity of T. pseudoexcavatum and T. indicum, in order to assess the capacity of both Chinese truffles to penetrate T. melanosporum plantations and habitats.
The following values have no corresponding Zotero field: accession-num: 18813959
Keywords: Chinese truffle; Ectomycorrhizae; Truffle cultivation; Truffle ecology; Truffle yield

New data on ectomycorrhizae and soils of the Chinese truffles Tuber pseudoexcavatum and Tuber indicum, and their impact on truffle cultivation. (Mycorrhiza, 2008)
Chinese truffles serve as a good complement to the market for Tuber melanosporum (Périgord black truffle). However, Chinese truffles could be introduced accidentally or fraudulently into the plantations of Mediterranean truffles, and they could have a negative effect on truffle production and natural ecosystems. The study of Tuber species from China which are commercialized in Europe began 14 years ago. Tuber pseudoexcavatum was proposed as a new species, and this has been validated by some authors based on molecular and phylogenetic studies. We synthesize their ectomycorrhizae using samples from the type collection, and we compare T. pseudoexcavatum and Tuber indicum ectomycorrhizae. The ectomycorrhizae of these species have a morphology which is related to the ectomycorrhizae of T. melanosporum. We provide useful information for the rapid screening of the above-mentioned Chinese truffles ectomycorrhizae, for the quality control of commercial plants mycorrhized with Tuber. Moreover, we analyze the soil tolerance and the host plant affinity of T. pseudoexcavatum and T. indicum, in order to assess the capacity of both Chinese truffles to penetrate T. melanosporum plantations and habitats.